A Note on the Operator-valued Poisson Kernel (European Journal of Pure and Applied Mathematics, 2009)
The purpose of this paper is to give a different proof of the integral formula\frac{1}{2π }\underset{0}{\overset{2π }{\int }}K_{r,t }(T )dt =I,where K_{r,t }(T ) is the operator-valued Poisson kernel.